2020
DOI: 10.1021/acs.biochem.0c00053
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Proton Transfer Controls Protein Structural Changes in Phytochrome

Abstract: Phytochromes are biological photoswitches that interconvert between two parent states (Pr and Pfr). The transformation is initiated by photoisomerization of the tetrapyrrole chromophore, followed by a sequence of chromophore and protein structural changes. In the last step, a phytochrome-specific peptide segment (tongue) undergoes a secondary structure change, which in prokaryotic phytochromes is associated with the (de)­activation of the output module. The focus of this work is the Pfr-to-Pr photoconversion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(82 citation statements)
references
References 46 publications
8
74
0
Order By: Relevance
“…Considering also the protonation state and processes, which play a crucial role in the photoconversion of phytochromes [20][21][22][23][24][25][26][27] and significantly change the spectral properties of the PCB molecule, Göller and co-workers, via semiempirical AM1 calculations, found three possible all-Z ground state species (in accordance with further experimental results, see below), which are depicted in Fig. 2 [18,28].…”
Section: Introductionsupporting
confidence: 73%
“…Considering also the protonation state and processes, which play a crucial role in the photoconversion of phytochromes [20][21][22][23][24][25][26][27] and significantly change the spectral properties of the PCB molecule, Göller and co-workers, via semiempirical AM1 calculations, found three possible all-Z ground state species (in accordance with further experimental results, see below), which are depicted in Fig. 2 [18,28].…”
Section: Introductionsupporting
confidence: 73%
“…
Fig. 1 Photocycle of bacterial phytochromes as derived from spectroscopic data 28 . In Agp2, Pfr is the stable dark state.
…”
Section: Mainmentioning
confidence: 99%
“…Together with vibrational spectroscopy studies 25 – 28 , it was thus possible to identify key structural elements in the chromophore binding pocket that are essential for communicating the light-induced structural changes of the chromophore to the tongue segment of the protein 29 . These are, inter alia, residues Y165, R211 and His278 and the propionic side chains B (prop B ) and C (prop C ) 17 , 25 , 27 , 28 , 30 . Specifically, prop C plays a remarkable role as it is protonated in Pfr but deprotonates with the decay of the Meta-F as a prerequisite for the structural conversion of the tongue.…”
Section: Mainmentioning
confidence: 99%
“…Proton release is observed to take place at the step from Meta-F to Pr state, when the photoreceptor becomes activated (72). Recently, it has been demonstrated that the pscC deprotonation of BV chromophore is essential for triggering a secondary structure change (73). In the case of prototypical phytochromes, it has been spectroscopically observed that one of the inner pyrrole rings transiently loses a proton during the transition from Meta-R to Pfr states (67,74).…”
Section: Pka Calculations Of Phytochromes With Poisson-boltzmann Elecmentioning
confidence: 99%